Peran Pelatihan AI Dan Pemasaran Media Sosial Dalam Membangun Kewirausahaan Digital Masyarakat RT 11 Meranti Sawah Lebar - Cici Permatasari; Arif Syaipul Hidayat; Dela Rahmadani; Lisa Aneka Oktapia; Andrew Samuel Indrata; Venny Novita Sari (Universitas Dehasen Bengkulu, 2026)
Digital transformationrequires society to be able to adapt to technological developments in order toincrease economic opportunities, particularly in strengthening digital-based entrepreneurship. This study aims to analyze the role of ArtificialIntelligence (AI) training and marketing through social media in building the capacity ofdigital entrepreneurship in the community of RT 11 Meranti Sawah Lebar. The research methodused a qualitative descriptive approach with data collection techniquesin the form of observation, in-depth interviews, and documentation ofbusiness actors and training participants. The results showed thatAI training improved digital literacy, work efficiency, and the ability toinnovate local products. Meanwhile, marketing through social media expandedmarket reach, increased interaction with consumers, and strengthenedthe brand identity of micro-businesses in the area. The integration of these twoaspects encourages an increase in community confidence inutilizing technology for economic activities. In conclusion, AI training andthe use of social media contribute significantly to the development ofdigital entrepreneurship in local communities, thus requiring program sustainabilityand institutional support to ensure a broader impact.